An fMRI Study of Adult Brain Cortical Activation Following Intensive Learning - Ahmed-Popova, Ferihan; Sivkov, Stefan; Topolov, Mariyan; Beshkov, Asen (Frontiers in Psychiatry, 2020)
Functional imaging techniques, fMRI in particular, has given the possibility to investigate non-invasively the cognitive processes in healthy populations and different disorders concerning neuro-psychiatry, thus unfolding the concepts guiding diagnosis and patient management. Different brain structures seem to support different types of cognitive functions in particular learning and memory thus the neurobiological explanation of the retrieval of information is associated with knowledge of brain plasticity, memory circuits, synaptic neurotransmission and the modulation of glial cells. Consistent with fMRI investigations of memory systems we tested the dependability of a memory paradigm using heterogeneous memory stimuli in order to find the neurobiological basis that correlates with memory task performance. Our study resulted with statistical significant differences in brain activations across the block design contrasts in both occipital and temporal regions in 29 mentally healthy students during a memory paradigm performance after intensive learning. As functional magnetic resonance imaging has become an important and reliable tool for investigation of brain anatomy and its function in health and disease, it becomes clear that further research of neurobiological basis of cognitive and memory domains can clarify different diagnostic prototypes and thus explain the human brain impairments in neuropsychological patients, since these are characterized by various cognitive dysfunctions.